EXPERIMENTAL EVALUATION OF THE INFLUENCE OF AROMATIC ESSENTIAL OILS ON THE AUTONOMIC REGULATION OF CARDIOVASCULAR AND RESPIRATORY FUNCTIONS - Shirmatova Madinabonu Odiljon kizi; Mukhamedieva Irodakhon Bakhtiyorkhoja Kizi (Innovate Conferences, 2025)
In recent years, the therapeutic potential of essential oils has gained significant attention in both experimental and clinical physiology. Aromatherapy has been recognized as a non-invasive method capable of modulating autonomic functions through olfactory and neurohumoral pathways. However, the comparative physiological effects of lavender, rosemary, and sage essential oils on the cardiovascular and respiratory systems remain insufficiently explored. Clarifying these interactions is of great importance for developing safe and effective complementary approaches to the prevention and management of functional disorders in the autonomic regulation of vital systems.